Update Breast Cancer 2022 Part 6 – Advanced-Stage Breast Cancer - Lüftner, Diana; Lux, Michael P.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Beierlein, Milena; Belleville, Erik; Untch, Michael; Thill, Marc; Ditsch, Nina; Aktas, Bahriye; Banys-Paluchowski, Maggie; Kolberg-Liedtke, Cornelia; Wöckel, Achim; Kolberg, Hans-Christian; Harbeck, Nadia; Stickeler, Elmar; Tesch, Hans; Hartkopf, Andreas D. (Geburtshilfe und Frauenheilkunde, 2023)
Large-scale study programs on CDK4/6 inhibitors, targeted therapies, and antibody–drug conjugates launched in recent years have yielded results from current studies which are now being published in journals and presented at international conferences. In this context, new results are available from the major CDK4/6 inhibitor studies. Also, an increasing amount of data is being published from large-scale genomic studies on efficacy and resistance mechanisms in patients treated with CDK4/6 inhibitors. These results now form the basis for further research plans to investigate combination therapies and treatment sequencing. Based on the latest published results, sacituzumab govitecan is now available as a second antibody–drug conjugate; this brings an advantage in terms of overall survival for patients with hormone receptor-positive (HRpos)/HER2-negative (HER2neg) breast cancer. In this review article, we summarize the latest developments and place them in context according to the current status of research.Die in den letzten Jahren begonnenen großen Studienprogramme zu den CDK4/6-Inhibitoren, den zielgerichteten Therapien und den Antikörper-Medikament-Konjugaten resultieren in Ergebnisse, die von aktuellen Studien auf internationalen Kongressen und Fachzeitschriften veröffentlicht werden. In diesem Zusammenhang sind neue Ergebnisse der großen CDK4/6-Inhibitor-Studien verfügbar. Auch werden zunehmend Daten von großen genomischen Studien zu Effektivitäts- und Resistenzmechanismen für Patientinnen, die mit CDK4/6-Inhibitoren behandelt worden sind, veröffentlicht. Basierend auf diesen Ergebnissen sollten nicht zuletzt Studien in Bezug auf Kombinationspartner und Therapiesequenzen geplant werden. Mit Sacituzumab Govitecan ist aufgrund neuester Veröffentlichungen nun ein zweites Antikörper-Medikament-Konjugat vorhanden, das bei hormonrezeptorpositiven (HRpos)/HER2-negativen (HER2neg) Patientinnen einen Gesamtüberlebensvorteil mit sich bringt. Diese Übersichtsarbeit fasst die neuesten Entwicklungen zusammen und ordnet sie in den aktuellen Forschungsstand ein.
Keywords: advanced breast cancer; chemotherapy; therapy standard